CYP2A6 gene polymorphisms impact to nicotine metabolism (Medical Journal of Indonesia, 2010)
Nicotine is a major addictive compound in tobacco cigarette smoke. After being absorbed by the lung nicotine is rapidly metabolized and mainly inactivated to cotinine by hepatic cytochrome P450 2A6 (CYP2A6) enzyme. Genetic polymorphisms in CYP2A6 may play a role in smoking behavior and nicotine dependence. CYP2A6*1A is the wild type of the CYP2A6 gene which is associated with normal or extensive nicotine metabolism. In the CYP2A6 gene, several polymorphic alleles have been reported such as CYP2A6*4, CYP2A6*7, CYP2A6*9, and CYP2A6*10 which are related to decreasing nicotine metabolism activity. The variation of nicotine metabolism activity could alter nicotine plasma levels. Smokers need a certain level of nicotine in their brain and must smoke regularly because of nicotine’s short half-life; this increases the number of smoked cigarettes in extensive metabolizers. Meanwhile, in slow metabolizers, nicotine plasma level may increase and results in nicotine toxicity. This will eventually lower the risk of dependence. (Med J Indones 2010; 19:46-51) Keywords: cotinine, hepatic cytochrome P450 2A6, smoking behavior